Formulasi Strategi Menggunakan Bisnis Model Canvas: Studi Kasus Pada Bisnis Distro di Jalan Padjajaran Bandung Jawa Barat - Sugiyanto; Muhammad Aditya Pratama; Endang Wahyuningsih (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
The fashion industry plays an important role in the growth of the national creative industry which absorbs a lot of employment. Business actors selected as samples of this study were 4 distribution stores (Distros), located on Jl Padjadjaran, Bandung. Increasingly fierce competition is a major problem, marked by declining income and profitability. The purpose of this research is to formulate a distribution business strategy using SWOT analysis and BMC. Qualitative and quantitative descriptive research approaches were used in this study. Qualitative research to identify the factors of strengths, weaknesses, opportunities and threats. The results of the study found several factors from the elements of the SWOT analysis, as a basis for conducting quantitative analysis, which resulted in an aggressive strategy that had to be developed. Based on this strategy it is formulated in the form of a business model canvas. The distros business needs to be developed more aggressively in terms of Customer Segment, value proposition, channels, and customer relationships so that company revenue can increase. Companies also need to emphasize the development of the aspects of key business activities, key partners and the effectiveness of utilizing key resources so that the company can carry out cost efficiency. The finding of this study is that BMC can be used to describe briefly but completely as an effort to formulate a strategy for the results of SWOT analysis.